ADOPT: A tool for automatic detection of tectonic plates at the surface of convection models. (30th August 2017) - Mallard, C.; Jacquet, B.; Coltice, N.
Abstract: Mantle convection models with plate‐like behavior produce surface structures comparable to Earth's plate boundaries. However, analyzing those structures is a difficult task, since convection models produce, as on Earth, diffuse deformation and elusive plate boundaries. Therefore we present here and share a quantitative tool to identify plate boundaries and produce plate polygon layouts from results of numerical models of convection: Automatic Detection Of Plate Tectonics (ADOPT). This digital tool operates within the free open‐source visualization software Paraview. It is based on image segmentation techniques to detect objects. The fundamental algorithm used in ADOPT is the watershed transform. We transform the output of convection models into a topographic map, the crest lines being the regions of deformation (plate boundaries) and the catchment basins being the plate interiors. We propose two generic protocols (the field and the distance methods) that we test against an independent visual detection of plate polygons. We show that ADOPT is effective to identify the smaller plates and to close plate polygons in areas where boundaries are diffuse or elusive. ADOPT allows the export of plate polygons in the standard OGR‐GMT format for visualization, modification, and analysis under generic softwares like GMT or GPlates. Key Points: Detection of tectonic plates at the surface of convection models It is based on image segmentation techniques to detect objects The detection tool is effective to identify and close plate polygons even on diffuse plate zones